TANTANGAN IMPLEMENTASI UNDANG-UNDANG PERBANKAN SYARIAH - Ali Maskur (Fakultas Ekonomika dan Bisnis, Universitas Stikubank, 2009)
DPR-RI legalize Law of Syariah Banking number 21/2008. It’s means thatsyariah banking has a foundation to develop the banking. The new substantial of the lawis including ‘syariah’ word for syariah banking, punishment for the leader ofstockholder, MUI has fatwa otority, The Central Of Bank as a controller and monitoringsyariah banking, definition of financing is changes, and there is choice of law inprinciple. In Implementation, the Law have two implementation i.e. policyimplementation and law enforcement implementation.To implementation the law needsother support until the target syariah banking of grow achieved. Syariah banking haschance and challenge. The challenge i.e there is foreign ownership, foreign employment,syariah principle on product/service by MUI, the leader of stockholder past a fit andproper test. The government support and banking syariah ability to overcome thechallenge is a key to speed of growth syariah banking.Key words: law of syariah bankin, MUI, central of bank, chance and challenge